Prediction of Infectious Complications after Percutaneous Nephrolithotomy - Chhetri, Raj Kumar; Baral, Suman; Thapa, Neeraj (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Post-operative infection is one of the most common and potentially life-threatening complications following percutaneous nephrolithotomy, ranging from Systemic inflammatory response syndrome (SIRS) to severe sepsis. It is reported to be the most common peri-operative cause of death. Despite taking utmost precautions, we come across major complications such as haemorrhage and urosepsis after percutaneous nephrolithotomy. This study aims to find the risk factors for infectious complications after percutaneous nephrolithotomy. Methods: This was an observational, cross-sectional, analytical study carried out in the Department of Surgery of Lumbini Medical College and Teaching Hospital over a period of six months. Pre- operative and intra-operative parameters of ninety-seven patients who underwent percutaneous nephrolithotomy were analysed to see the association between perioperative and intraoperative factors in development of post-operative infectious complications. Results: Post-operatively, SIRS was observed in 28.9% of the patients and 6.2% developed post operative sepsis. Stone burden, types of stone, abnormal urinalysis and mean operative time were associated with post-operative SIRS while stone burden, abnormal urinalysis, positive urine culture and operation time were statistically associated with post-operative sepsis. In univariate analysis only mean operation time and mean stone burden were statistically associated in development of post operative SIRS and sepsis. Conclusion: In the present study mean operation time and mean stone burden were found to be the predictive factors for post-operative infectious complications after percutaneous nephrolithotomy.